The efectiveness of dry cupping and hot pack on pain relief and reduced functional disability for patients with non-specific low back pain - Azira Iqlima Razali (2021)
The objective of this study was to identify the effectiveness of dry cupping and hot pack on pain relief and reduced functional disability for patients with non-specific low back pain. The study design was experimental study using pre-test and post-test measurements. A total of 39 patients with non-specific low back pain from Sultan Idris Education University, Malaysia who fulfilled the inclusion criteria were recruited as subjects using purposive sampling methods. The subjects were randomly assigned equally (N=13) into dry cupping group, hot pack group and control group. Dry cupping group received a treatment session in a week for three weeks, hot pack group received two treatment sessions twice a week, and control group received no treatment, but continue previous treatment from general practitioner. Numerical Pain Rating Scale was used to measure pain intensity and Oswestry Disability Index was used to measure functional disability before and after the intervention for all three groups. Data was analysed using one-way ANOVA with significant level predetermined at <0.01 prior to study. The study findings revealed that patients in both dry cupping group and hot pack group indicating significant differences on pain relief [F (21.331), = 0.000] and reduced functional disability [F (18.046), = 0.000] after completing three weeks interventions when compared with control group. Dry cupping and hot pack treatments are found to be equally effective, thus, both treatments could be suggested for pain relief and to reduce functional disability for patients with non-specific low back pain. The researcher is suggesting to health care professionals to consider dry cupping therapy as one of the alternative treatment options in treating patients with non-specific low back pain in order to relieve pain and to reduce functional disability.